2017
DOI: 10.18632/oncotarget.21790
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of the genes ataxin 2 like,ATXN2L, and Janus kinase 2,JAK2, in cutaneous CD4 positive T-cell lymphoma

Abstract: Acquired mutations were recently described in cutaneous T-cell lymphomas for the JAK1, JAK3, STAT3, and STAT5B genes of the JAK-STAT pathway. In the present study, RNA-sequencing of a primary cutaneous CD4 positive T-cell lymphoma carrying a three-way t(9;13;16)(p24;q34;p11) chromosome translocation showed that JAK2 from chromosome band 9p24 was rearranged and fused to a novel partner gene, ATXN2L, from 16p11. RT-PCR together with Sanger sequencing verified the presence of the ATXN2L-JAK2 fusion transcript. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Recently, ataxin-2-like (ATXN2L) was discovered as a novel regulator of SG 6 . It was reported that ATXN2L was widely expressed in immortalized cell lines, and ATXN2L-JAK2 fusion was found in CD4-positive T-cell lymphoma 8 . ATXN2L is a paralog of Ataxin-2 (ATXN2) but without abnormal polyQ expended track, which is conserved in most of the ATXNs and drives the pathogenesis of neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ataxin-2-like (ATXN2L) was discovered as a novel regulator of SG 6 . It was reported that ATXN2L was widely expressed in immortalized cell lines, and ATXN2L-JAK2 fusion was found in CD4-positive T-cell lymphoma 8 . ATXN2L is a paralog of Ataxin-2 (ATXN2) but without abnormal polyQ expended track, which is conserved in most of the ATXNs and drives the pathogenesis of neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…RNA sequencing was performed as described in detail previously [ 11 ]. Total RNA was extracted from the patientÂŽs bone marrow cells at the time of secondary MDS diagnosis using miRNeasy Mini Kit (Qiagen Nordic, Oslo, Norway) and one ÎŒg was sent to the Genomics Core Facility at the Norwegian Radium Hospital, Oslo University Hospital ( http://genomics.no/oslo/ ) for high-throughput paired-end RNAsequencing.…”
Section: Methodsmentioning
confidence: 99%
“…These techniques have impacted every field of molecular research, escalating previously used sequencing technologies [ 11 ], and opening the way to the -omic sciences foundation [ 1 , 2 ]. Indeed, NGS methods allow the sequencing of entire genomes [ 12 , 13 , 14 , 15 ], of exomes [ 16 , 17 , 18 ], of panels of genes related to a disease of interest [ 19 , 20 , 21 ], or of a single gene [ 22 , 23 , 24 , 25 , 26 ], but can also be used to explore the entire transcriptome [ 27 , 28 , 29 ], small RNAs [ 30 , 31 , 32 ], the epigenome [ 33 , 34 ], and the microbiome [ 35 , 36 , 37 , 38 ].…”
Section: High-throughput Analysesmentioning
confidence: 99%
“…In addition to the study of sequence variations at the DNA level, NGS methods can be used to study genetic variability, and the mechanisms underlying the onset of specific diseases at epigenetic, transcriptomic and metagenomic levels [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Indeed, several factors, other than individual genetic predisposition, such as diet, environmental factors and lifestyle, can influence the epigenome, the transcriptome and the microbiome [ 2 , 50 ].…”
Section: High-throughput Analysesmentioning
confidence: 99%
See 1 more Smart Citation